Impact on prognosis of unexpected uterine sarcoma with scalpel morcellation or enucleation - Terumi Tanigawa; Kohei Omatsu; Yoichi Aoki; Atsushi Fusegi; Makiko Omi; Sachiho Netsu; Sanshiro Okamoto; Mayu Yunokawa; Hidetaka Nomura; Hiroyuki Kanao (Gynecologic Oncology Reports, 2022)
Objective: It is well known that power morcellation of unexpected uterine sarcoma affects prognosis. There are few reports on the effects of scalpel morcellation or myomectomy of uterine sarcoma on prognosis, which is not well understood. This study investigated the effect on recurrence and prognosis when tumors of uterine sarcoma undergo scalpel morcellation or myomectomy. Methods: We performed a retrospective, observational study by collecting data from the medical records of patients who were histologically diagnosed with uterine sarcoma at our hospital between 2005 and 2017. All patients with unexpected uterine sarcoma were diagnosed after laparoscopic hysterectomy with scalpel morcellation or myomectomy (abdominal and laparoscopic) for presumed myoma. We evaluated recurrence rate, recurrence site, progression-free survival (PFS), and overall survival (OS). Results: A total of 15 patients were examined in this study. Twelve patients underwent myomectomy (7 patients with open surgery, 5 patients with laparoscopic surgery), and 3 patients underwent total laparoscopic hysterectomy with transvaginal scalpel morcellation. There were 11 cases of recurrence, and the recurrence rate was 78 %. The recurrence site was peritoneal dissemination in 10 cases (91 %) and lymph node metastasis in 1 case (9 %). The median PFS was 32 months [95 % confidence interval (CI) = 6.5-NA], and the median OS was 95.5 months [95 % CI = 55.8-NA]. Conclusion: Power morcellation, scalpel morcellation, and myomectomy may affect recurrence and prognosis. Further studies are needed in the future.